Proceedings of the International Conference on Tourism, Economics, Accounting, Management, and Social Science (TEAMS 2018) 2019
DOI: 10.2991/teams-18.2019.24
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fraud Triangle and Theory of Planned Behavior on Students Academic Fraud in Bali

Abstract: This study aims to find out the effect of Fraud Triangle (X1) and Theory of Planned Behavior (TPB) (X2) on Academic Fraud (Y) by college students in Bali. The result of this study was hoped in providing the input for the lecturers in the learning process, especially when presenting the midterm or final exams. The instrument in this study was a questionnaire with a Likert scale with the validity and reliability tests were tested first. .The data analysis technique used was multiple regression analysis technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Generally, students with good subjective norms always want to behave well; fulfilling this behavior is known as fulfilling normative beliefs. Previous research found a positive relationship between subjective norms and intentions (Meitriana et al, 2019;Fang et al, 2017).…”
Section: Discussionmentioning
confidence: 87%
“…Generally, students with good subjective norms always want to behave well; fulfilling this behavior is known as fulfilling normative beliefs. Previous research found a positive relationship between subjective norms and intentions (Meitriana et al, 2019;Fang et al, 2017).…”
Section: Discussionmentioning
confidence: 87%
“…These pressures and opportunities, coupled with their ability to rationalize their actions before execution, complement the occurrence of fraud (Bicer, 2020; Dellaportas, 2013; Shbail et al , 2022). In practice, it turns out that the fraud triangle has been used by many people, including in the educational sphere, which has examined cheating behavior using the fraud triangle model (Bicer, 2020; Maria et al , 2022; Meitriana et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is important to note that rationalization is difficult to see and observe, as is the impossibility of reading the minds of con artists. In this case it will be very different from one person to another because what is rational for one person is not necessarily for another (Meitriana et al, 2019).…”
Section: Opportunitymentioning
confidence: 99%